High altitude as a possible factor for dysbiosis of salivary microbiome in orthodontic patients. (November 2020) - AlShahrani, Ibrahim; Hosmani, Jagadish; AlShahrani, Abdulaziz; Togoo, Rafi Ahmad; Syed, Sadatullah; Yassin, Syed M.; Chandramoorthy, Harish C.; Devaraj, Anantharam
Highlights: Biodiversity of salivary microbiome reflect the healthy state of the oral cavity. Influence of high altitude and orthodontic appliance on saliva microbiome analysed. Dysbiosis was noticed in saliva microbiome of high altitude orthodontic patients. High altitude, hypoxic condition and orthodontic appliance could be detrimental. Abstract: Background: External stressors such as high altitude and low oxygen are known to affect the human microbiome, and in light of the increased occurrence of dental caries and periodontitis in orthodontic patients, the effect of high altitude and the altered oral environment in orthodontic patients on the oral salivary microbiome was researched. Materials & methods: 31 orthodontic patients from high altitude, Aseer region and 25 orthodontic patients, residing at sea level, as controls were included. DNA isolation was done from the saliva collected from the study participants. V3 area of 16s RNA was targeted by universal primers through PCR to decipher the salivary microbiome in both the groups. Results: A total of 11 genera belonging to 4 phyla of bacteria were identified in both groups. The most abundant microbiome at the phylum level was: Firmicutes, Bacteroidetes Proteobacteria, and Cyanobacteria. The salivary microbiome was more diverse in sea level controls compared to that of the orthodontic patients at high altitude wherein the presence of only two main phyla: Firmicutes and Proteobacteria were seen. The controls revealed Firmicutes, Proteobacteria, Bacteroidetes and Cyanobacteria. Conclusions: The findings of the study suggest that the biodiversity of the salivary microbiome is severely perturbed under the cumulative influences of high altitude and presence of fixed orthodontic appliance. Under these circumstances, a strict and meticulous oral hygiene regimen should be recommended and followed to avoid harmful effects on the periodontal tissues.